Effect of Probiotics on the Growth of Vannamei Shrimp - Atma Jaya Salaman Muin; Ade Muharam; Mulis Mulis (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the proper concentration of probiotics in the maintenance of vannamei shrimp (Litopenaeus vannamei) and see the effectiveness of local probiotics given to growth and survival rate (SR). This research was conducted in June - July 2016. The method used was an experimental method with 4 treatments and 3 replications. The design used in this study is a Completely Randomized Design (CRD), using Analysis of Variance (ANOVA). The results showed that the addition of probiotics in each treatment, based on the analysis of various data, had no significant effect. The highest absolute weight growth was aimed at treatment A (0.2 ml / m3) which was 10.42 grams, followed by treatment C (0.6 ml / m3) 7.02 grams, B (0.4 ml / m3) 6.99 grams, and the lowest treatment D (0 ml / m3) 6.98 grams. The highest absolute length growth was aimed at treatment C, namely (0.6 ml / m3) 5.16 cm, followed by treatment A (0.2 ml / m3) 5.08 cm, D (0 ml / m3) 4.83 cm, and the lowest treatment B (0.4 ml / m3) 4.64 cm. The highest survival rate was in treatment A (0.2 ml / m3) which was 97%, followed by treatment B (0.4 ml / m3) 83%, D (0 ml / m3) 80% and lowest C (0.6 ml / m3) 73%. Keywords: Probiotic; shrimp; vannamei; growth; survival.